Autour de la Syrie médiévale : études offertes à Anne-Marie Eddé - Boudier, Mathilde; Eddé, Anne-Marie (Orient & Méditerranée, 2022)
On the occasion of Anne-Marie Edde's retirement in June 2018, her colleagues, friends and students gathered at the Sorbonne for a one-day workshop. This book brings together the contributions that made this day so rich, inspired by different aspects of her research as a historian. The summary of her career as a professor, researcher and director of the IRHT (Institut de recherche et d'histoire des textes) is accompanied by a bibliography of her work. Among the eleven contributions, four are devoted to the history of medieval Bilad al-Sham - from Umayyad Damascus and Abbasid Syria, through the letters of al-Awza'i, to Mamluk Aleppo and Ottoman Mount Lebanon. In the wake of Saladin (2008), two authors reflect on biographical writing in history. The forms and representations of power in Islam are the subject of the ensuing two studies. Finally, three articles of varia broaden the horizon to Florentine commercial archives, French military archives in Algeria, and archaeology.